Rapid Source Characterization of the 2023 6.8 Al Haouz, Morocco, Earthquake - William L. Yeck; Alexandra E. Hatem; Dara E. Goldberg; William D. Barnhart; Jessica A. Thompson Jobe; David R. Shelly; Antonio Villaseñor; Harley M. Benz; Paul S. Earle (The Seismic Record, 2023)
The U.S. Geological Survey (USGS) National Earthquake Information Center (NEIC) estimates source characteristics of significant damaging earthquakes, aiming to place events within their seismotectonic framework. Contextualizing the 8 September 2023, Mw 6.8 Al Haouz, Morocco, earthquake is challenging, because it occurred in an enigmatic region of active surface faulting, and low seismicity yet produced significant damage and loss of life. Here, we present the rapid earthquake source products produced by the USGS NEIC, describing how the source model was derived using both seismic and geodetic observations. Our analysis indicates that the earthquake was the result of oblique-reverse faulting in the lower crust on either a steeply north-dipping fault or a moderately south-dipping fault. Finite-slip models using seismic and geodetic data reveal a compact source, with slip occurring at depths of 15–35 km. The causative fault is not apparent, because the rupture did not break the surface, and it is not possible to definitively attribute the earthquake to a known structure. The earthquake centroid depth of 25 km is noteworthy, because it shows slip extending beyond common estimates of seismogenic depth. This earthquake highlights that the seismogenic processes associated with mountain building in this wide plate boundary region are poorly understood.